2015
DOI: 10.1088/0953-4075/48/16/165503
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for observing dynamical and anti- dynamical Casimir effects in circuit QED due to fast modulation of qubit parameters

Abstract: We consider the nonstationary circuit QED architecture, where a single artificial two-level atom interacts with a cavity field mode under external modulation of one or more system parameters. Two different approaches are employed to study the effects of Markovian dissipation on modulationinduced transitions between the atom-field dressed states: the standard master equation of Quantum Optics and the recently formulated dressed-picture master equation. We estimate the associated transition rates and show that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 57 publications
1
48
0
4
Order By: Relevance
“…We did solve it numerically and verified that for the parameters of Figs. 1 and 2 the results are almost indistinguishable from the predictions of a much simpler 'standard master equation' of Quantum Optics: [38,40,83,86] …”
Section: Account Of Dissipationmentioning
confidence: 72%
See 1 more Smart Citation
“…We did solve it numerically and verified that for the parameters of Figs. 1 and 2 the results are almost indistinguishable from the predictions of a much simpler 'standard master equation' of Quantum Optics: [38,40,83,86] …”
Section: Account Of Dissipationmentioning
confidence: 72%
“…However, in Refs. [37][38][39]85] the authors showed that the number of excitations can be reduced instead, in what they called ADCE. This effect consists of coherent annihilation of two system excitations due to the approximate transition |g, n ←→ |e, n − 3 (for n ≥ 3), and takes place for the modulation frequency η ADCE ≈ 3ω − Ω 0 .…”
Section: Model a Atom-field Interactionmentioning
confidence: 99%
“…For adiabatic variation of η only a few photon states are populated at a time (see 4c for the photon statistics at the time instants βt = 15 and 30), which is reflected in the sub-Poissonian photon statistics for large times. The amount of created photons can substantially exceed the average photon number achievable for the harmonic modulation with constant frequency [27,28] (green lines in 4a and 4b, for which η was found numerically to optimize the photon generation). Our numerical simulation of dissipation is not accurate for large photon numbers, so we only show the dissipative dynamics for βt < 21.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Hence the dissipation must be sufficiently weak and the frequency of modulation must be tuned with a high precision, typi-cally of the order of 10 −100 kHz for modulation frequencies in the GHz range, that ultimately should be determined experimentally or numerically. For the harmonic modulation of system parameters the observable quantities, e. g., the average photon number or the atomic excitation probability, exhibit a oscillating behavior as function of time [5,28]. Therefore the duration of modulation must also be minutely adjusted to grasp a meaningful amount of excitations, since the detection is typically carried out when the modulation has ceased.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that DCE could be implemented even using a single two-level atom (qubit) with time-dependent parameters, such as the transition frequency or the atom-field coupling strength [22][23][24][25][26]. Generation of excitation from vacuum occurs due to the counter-rotating terms in the Rabi Hamiltonian, which for many years had been neglected under the Rotating Wave Approximation.…”
Section: Introductionmentioning
confidence: 99%